Pyridone substituted phthalocyanines: Photophysico-chemical properties and TD-DFT calculations - (:unkn) unknown (WORLD SCI PUBL CO INC, 2018)
A 4-(6-methyl-3-nitro-2-oxo-1,2-dihydropyridin-4-yloxy)phthalonitrile has been used to prepare a novel Zn(II) phthalocyanines with four peripheral pyridone substituents. The compound has been characterized by UV-visible absorption, FT-IR and H-1-NMR spectroscopy, elemental analysis and MALDI-TOF mass spectroscopy. The fluorescence, triplet quantum and singlet oxygen quantum yields have been determined and TD-DFT calculations have been used to identify trends in the electronic structure.
Keywords: phthalocyanines; pyridones; TD-DFT calculations; singlet oxygen; photophysics